BALRAM’S STRATEGY OF USING SYMBOLIC CAPITAL IN ADIGA’S THE WHITE TIGER - Apsari Fajar Prihantini; Sri Nurhidayah (Fakultas Bahasa dan Seni UNP, 2019)
This research focuses on exploring Balram’s success from the factor of his strategy in using symbolical capital. Society lives in the field where symbolic capital impact over the other capital. It can be also reflected in the story, from Balram’s life to the other characters he witnessed. Therefore, this research’s problem focuses on how Balram uses symbolic capital as his strategy to survive in society in Aravind Adiga’s The White Tiger. To accommodate the analysis, the research uses Bourdieu’s theory of symbolical capital that explains its importance for Balram. This research is qualitative and the approach is phenomenological approach. The data are the quotation from the novel. The source of the data is Adiga’s The White Tiger. The technique of data collection is documentation. The technique of data analysis is interpretation. Based on the analysis, it can be resulted that symbolic capital is crucial to drag up someone’s life. Symbolic capital can be used as the strategy (class distinction) to survive in the field where capital is exchanged. Balram’s driving certificate, status, environment, and others have exposed how it adheres symbolical status. Other characters are also helpful in explaining how symbolical capital affects their life, especially in the issue of dominance.